Training on Artificial Intelligence Integration in Lesson Planning and Assessment for Madrasah Diniyah Darul Huda Teachers - Saidah Munawaroh; Zulfan Syahansyah (Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2026)
Education in Salaf Islamic boarding schools, specifically Madrasah Diniyah (Madin) Darul Huda, faces a digital divide challenge where the learning process remains dominated by manual, conventional methods. This leads to inefficiency in lesson planning and subjectivity in student assessment. This community service program aims to enhance the competence of Madin teachers in integrating Artificial Intelligence (AI) technology to optimize learning without eroding the values of the Salafiyah tradition. The implementation method employs a participatory approach consisting of preparation, basic training, hands-on workshops using generative AI tools (such as ChatGPT and Gemini), implementation mentoring, and evaluation. The results indicate an improvement in teachers' digital literacy in designing innovative curricula and data-driven assessment instruments. Through this integration, learning administration efficiency is increased, creating a boarding school education model that is adaptive to modern developments while maintaining the essence of Islamic character education.